Comparison of Support Vector Machine and XGBSVM in Analyzing Public Opinion on Covid-19 Vaccination - Rahmaddeni, Rahmaddeni; Anam, M. Khairul; Irawan, Yuda; Susanti, Susanti; Jamaris, Muhammad (Prodi Teknik Informatika FIK Universitas Muslim Indonesia, 2022)
The corona virus has become a global pandemic and has spread almost all over the world, including Indonesia. There are many negative impacts caused by the spread of COVID-19 in Indonesia, so the government takes vaccination measures in order to suppress the spread of COVID-19. The public's response to vaccination was quite diverse on Twitter, some were supportive and some were not. The data used in this study came from Twitter which was taken using the drone emprit portal, using the keyword, namely